EVALUASI JARINGAN IRIGASI SALURAN SEKUNDER NGABEAN KABUPATEN NGAWI PADA D.I. SALURAN INDUK MADIUN: Evaluation Of Ngabean Secondary Canal Irrigation Network, Ngawi District On Saluran Induk Madiun Irigation Area - Dewi Nusantara, Danayanti Azmi; Poppy Fajar Putri Hartiningsih (Jurnal Rekayasa Infrastruktur HEXAGON, 2024)
Ngabean Secondary Canal which is located in Ngawi Regency receives main water supply from Jati Dam amounting to 25% of the main dam discharge and water withdrawal from the Ngabean Dam intake of 0.45 m3/ha. However, this value does not meet the water needs of the entire irrigation area. Apart from that, the Ngabean Secondary Canal also experienced a reduction in the irrigation area from 1840 ha to 1818 ha. From the results of the analysis that has been carried out, in conditions before rehabilitation, the highest dependent flow of Jati Dam was 1.01 m3/s and the lowest was 0.00 m3/s with water withdrawal at the intake of 25%, able to fulfill the planting pattern of paddy(15%)-crops(75%)-crops(50%) generated a production profit of IDR 8.794.123.880,00. Meanwhile, after rehabilitation, the highest was 5.93 m3/s and the lowest was 3.21 m3/s with an intake of 32%, able to fulfill the planting pattern of paddy(100%)-paddy(100%)-paddy(100%) resulting in a production profit of IDR 83,564,115,480.00 with the highest irrigation water requirement value of 3.10 m3/sec. Apart from that, the existing canal dimensions still meet the requirements after land reduction so that no changes to the canal dimensions are required.